30. FLOW DIVERSION STENT: AN INNOVATION IN TREATMENT OF COMPLICATED CEREBRAL ANEURYSMS (Vietnam Journal of Community Medicine, 2024)
Brain aneurysm is an abnormal localized dilation of an artery in the brain that, when ruptured, causes bleeding in the brain and can lead to stroke, coma and/or death. The flow diversion stent is an invention equipment that helps optimize treatment results with types of aneurysms that cannot be treated with previous intervention methods. They gradually create thrombus in the aneurysm, supporting the growth of neointima and thereby completely occluding the aneurysm.Technical characteristics and mechanism of action: They have higher metal surface area coverage (about 30-35%) compared to previous generation stents that have about 8-100% metal surface area coverage 10%. They are placed across the neck of the aneurysm and divert blood flow away from the aneurysm, causing blood stagnation in the aneurysm, which then leads to an inflammatory response, followed by thrombosis and “thrombosis.” “heal” aneurysm. Besides, they also regenerate the endothelium of the parent artery, eliminating aneurysms from the circulationSafety: Aneurysm rupture is one of the most serious complications that can cause massive intracranial hemorrhage and death. From the Retrospective Analysis of Late Aneurysm Rupture (RADAR), late aneurysm rupture after flow-switching stent use occurred in 1.0% of patients and late parenchymal hemorrhage was reported in 1.9% of patients.Conclusion: Treatment of cerebral aneurysms with flow-switching stents is a feasible and effective technique for unruptured aneurysms. However, the experience is still new and the follow-up period is short. Therefore, further studies with longer follow-up time are needed to determine the rate of complete obstruction.
Keywords: Flow diversion stent; cerebral aneurysm; neurological intervention